Environmental catastrophes, climate change, and attribution. Issue 1 (11th February 2020) - Lloyd, Elisabeth A.; Shepherd, Theodore G.
Abstract: In our discussion of environmental and ecological catastrophes or disasters resulting from extreme weather events, we unite disparate literatures, the biological and the physical. Our goal is to tie together biological understandings of extreme environmental events with physical understandings of extreme weather events into joint causal accounts. This requires fine‐grained descriptions, in both space and time, of the ecological, evolutionary, and biological moving parts of a system together with fine‐grained descriptions, also in both space and time, of the extreme weather events. We find that both the "storyline" approach to extreme event attribution and the probabilistic "risk‐based" approach have uses in such descriptions. However, the storyline approach is more readily aligned with the forensic approach to evidence that is prevalent in the ecological literature, which cultivates expert‐based rules of thumb, that is, heuristics, and detailed methods for analyzing causes and mechanisms. We introduce below a number of preliminary examples of such studies as instances of what could be pursued in the future in much more detail. Abstract : In our discussion of environmental and ecological catastrophes or disasters resulting from extreme weather events, we unite disparate literatures, the biological and the physical. Our goal is to tie together biological understandings of extreme environmental events with physical understandings of extreme weather events into joint causal accounts.